The representation of alterity : aspects of subjectivity in Schubert's second Moment musical and Wilde's 'The Nightingale and the Rose' - Van der Mescht, Heinrich Hermann (University of Pretoria, 2013)
Dissertation (MMus)--University of Pretoria, 2010.